SPEED-3D: a geographic routing protocol for 6LoWPAN networks. (2015) - Bocchino, Stefano; Petracca, Matteo; Pagano, Paolo; Ghibaudi, Marco; Lipari, Giuseppe
The integration of the wireless sensor network (WSN) technology in the internet world is a necessary step towards the full accomplishment of the internet of things (IoT) vision. In order to reach a seamless integration of tiny mote devices in internet, the IPv6 addressing method and communication protocols developed for the IoT must be modified or adapted to match the WSN requirements. This adaptation process is started in the 2007 with the standardisation of the IPv6 protocol over low power wireless personal area networks (6LoWPAN). In such a scenario, we propose SPEED-3D, an extension of the SPEED geographic routing algorithm, adapted to 6LoWPAN networks that caters for 3D routing. SPEED-3D avoids the creation of routing tables, and has a very low memory occupation; it also supports load balancing and flow shaping; finally, thanks to the presented extension, it is able to work seamlessly in a 3D setting (e.g., a tall building). In the paper, we first present SPEED-3D in 6LoWPAN networks by detailing the encapsulation of all messages in the IEEE802.15.4 medium access control (MAC) protocol and the new functionality provided thanks to the IPv6 standard, then we present its implementation on a real-time kernel and its performance in a realistic indoor scenario.